2015
DOI: 10.3109/00016357.2015.1099730
|View full text |Cite
|
Sign up to set email alerts
|

Sleep quality in patients with xerostomia: a prospective and randomized case-control study

Abstract: Objectives To investigate sleep quality, anxiety/depression and quality-of-life in patients with xerostomia. Materials and methods This prospective, observational, cross-sectional study was conducted among a group of xerostomia patients (n = 30) compared with 30 matched control subjects. The following evaluation scales were used to assess the psychological profile of each patient: the Hospital Anxiety and Depression Scale, the Oral Health Impact Profile-14 (OHIP-14), the Xerostomia Inventory, the Pittsburgh Sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
0
14
0
Order By: Relevance
“…In this sample we have previously reported a significant increased risk for xerostomia and sleep disturbances among the CA group [3]. Sleep disturbances related to xerostomia have been mentioned in different medical condition [40][41][42][43]. Sleep disturbances in relation to caries activity must be considered unique and the relationship to general health needs more research.…”
Section: Discussionmentioning
confidence: 90%
“…In this sample we have previously reported a significant increased risk for xerostomia and sleep disturbances among the CA group [3]. Sleep disturbances related to xerostomia have been mentioned in different medical condition [40][41][42][43]. Sleep disturbances in relation to caries activity must be considered unique and the relationship to general health needs more research.…”
Section: Discussionmentioning
confidence: 90%
“…Hyposalivation as well as xerostomia, may also affect other oral functions such as chewing, swallowing and denture wearing and may also increase the risk for both dental caries and erosion . In 50‐ to 75‐year‐old subjects other oral symptoms like burning mouth, difficulties in opening the mouth and gum bleeding as well as intake of medications and the habit of smoking have been shown to be related to xerostomia, especially during the night …”
Section: Introductionmentioning
confidence: 99%
“…Another important finding is that the biggest effect and score difference were obtained in the malic acid lozenge group for the psychological discomfort dimension of the OHIP‐14‐PT. This is noteworthy because it has been suggested that patients with xerostomia experience an increased prevalence of anxiety and depression (Lopez ‐Jornet et al, ). In the malic acid lozenge group, the difference was nearly twice the MID, suggesting that the GSSS from this group provide considerable improvement in this dimension.…”
Section: Discussionmentioning
confidence: 94%